Energy-Based Practices and the Medicine of Movement—The Cases of 5Rhythms and Core Energetics - Géraldine Mossière (Religions)
This paper discusses the role of energy and movement in facilitating experiences of well-being from an anthropological perspective that considers energy as a situated form of knowledge. Drawing on fieldwork among Core Energetics (CE) and 5Rhythms (5R) groups, I examine how the circulation of energy is achieved through bodily movements and dances, attention to the senses, somatic self-cultivation, and deep experiences of consciousness. Focus is hold on the ritual elements, including a specific spacetime framework and intersubjective exercises that facilitate energetical experiences that renew the subjective and intersubjective relationship to the self in a restorative way. I argue that mind–body–energy groups conflate two Western sources: on the one hand, the legacy of early Western medical offshoots that have been marginalized by mainstream biomedicine, and on the other, discursive references to contemporary interpretations of quantum physics.